How long do percutaneous endoscopic gastrostomy feeding tubes last? A retrospective analysis. Issue 1114 (24th July 2018) - Siau, Keith; Troth, Tom; Gibson, Elizabeth; Dhanda, Anita; Robinson, Lauren; Fisher, Neil C
Abstract: Background: Percutaneous endoscopic gastrostomy (PEG) tubes allow for long-term enteral feeding. Disk-retained PEG tubes may be suitable for long-term usage without planned replacement, but data on longevity are limited. We aimed to assess the rates and predictors of PEG longevity and post-PEG mortality. Design: Single-centred retrospective cohort study of patients with disk-retained (Freka) PEG tubes. Methods: All patients undergoing PEG between 2010 and 2013 were identified, and retrospective analysis of outcomes until 2017 (median 1062 days) was performed. Time-to-event data were plotted using Kaplan-Meier curves, with predictors of survival derived from multivariate Cox-regression analyses. Results: 277patients were studied, with a median age of 74 years (IQR 59–82). PEG tube failure occurred in 17.4%, due to: buried bumper syndrome (7.0%), split/broken tube (6.3%), peristomal infection (1.8%) and dislodged tube (1.1%). PEG tube longevity was 95.1% (1 year) and 68.5% (5 year), with age <70 (HR 2.65, 95% CI 1.25 to 5.62, p=0.011) being predictive of PEG failure. Post-PEG mortality was 10.5% (30 day), 35.4% (1 year) and 59.7% (5 year). Age ≥70 was associated with mortality (HR 2.79, 95% CI 1.92 to 4.05, p<0.001), whereas PEG failure (HR 0.46, 95% CI 0.27 to 0.77, p=0.003) and elective PEG removal (HR 0.23, 95% CI 0.08 to 0.64, p=0.005) were associated with reduced mortality. Conclusions: 68.5% of PEG tubes remain intact after 5 years. Younger age was associated with earlier PEG failure, whereas younger age, PEG replacement and elective PEG tube removal were associated with improved survival. These data may inform future guidance for elective PEG tube replacements.